2005
DOI: 10.1099/ijs.0.63325-0
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence phylogenetic study of the genus Haemophilus with description of Haemophilus pittmaniae sp. nov.

Abstract: Multilocus sequence phylogenetic study of the genus Haemophilus with description of Haemophilus pittmaniae sp. nov. The phylogeny of human isolates of Haemophilus species was estimated based on partial sequences of four separate housekeeping genes. The clustering of each set of sequences was in accordance with speciation of the strains with few exceptions: of 108 gene fragments examined, only three appeared to have been subject to recombination events across the species barrier. Housekeeping gene similarity su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 26 publications
4
58
0
Order By: Relevance
“…Recently, Nørskov-Lauritsen et al (42) defined the relationships of human-specific haemophili within the family Pasteurellaceae by performing MLSA with partial, concatenated adk, pgi, recA, and infB gene sequences. Since this approach revealed that both H. influenzae and H. haemolyticus were present in an Haemophilus sensu stricto phylogenetic cluster and were separate from other members of the family, we have used it to determine if the NT H. influenzae and H. haemolyticus (hemolytic and nonhemolytic) strains in our study also maintain the same relationships.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Nørskov-Lauritsen et al (42) defined the relationships of human-specific haemophili within the family Pasteurellaceae by performing MLSA with partial, concatenated adk, pgi, recA, and infB gene sequences. Since this approach revealed that both H. influenzae and H. haemolyticus were present in an Haemophilus sensu stricto phylogenetic cluster and were separate from other members of the family, we have used it to determine if the NT H. influenzae and H. haemolyticus (hemolytic and nonhemolytic) strains in our study also maintain the same relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Partial DNA sequences of the adk, pgi, recA, and infB genes were generated for MLSA according to the strategy used by Nørskov-Lauritsen et al (42), with the exception that the oligonucleotides used for PCR amplification of these genes in the present study were based on sequences from H. influenzae strain Rd ( Table 2). The oligonucleotides used for PCR amplification of the partial 16S rRNA gene sequences for the differentiation of Haemophilus species have been described previously (32) ( (42) and for infB (20). The 16S rRNA gene sequences for a subset of these strains ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Nørskov-Lauritsen et al (2005), four genes were used for MLSA comparison to describe the novel species Haemophilus pittmaniae, supporting DNA-DNA hybridization results. Three of the housekeeping genes were selected from the multilocus sequence typing (MLST) study of Haemophilus influenzae (Meats et al, 2003).…”
Section: Taxonomic Investigation At the Species Levelmentioning
confidence: 99%
“…As a result of improved sequencing technologies, identification based on sequence comparisons of multiple housekeeping genes has become technically and economically feasible. Multilocus sequence analysis (MLSA) eliminates the potential problems resulting from homologous recombination and has been applied with success in the identification of several bacterial species that are difficult to differentiate by simpler methods (5,13,17,18,23,29,25,33). Schemes based on four to seven gene loci have proven valuable in differentiation of Streptococcus species (5, 17, 18).…”
mentioning
confidence: 99%